2010
DOI: 10.1002/acp.1724
|View full text |Cite
|
Sign up to set email alerts
|

Investigators under influence: How social norms activate goal-directed processing of criminal evidence

Abstract: Previous research has shown that exposure to social information can influence behaviour through the automatic activation of goals. In the first study to examine such influences in a legal setting, an experiment with 104 experienced criminal investigators tested the idea that exposure to occupational norms can activate distinct information-processing goals. As predicted, exposure to norms associated with efficiency (vs. thoroughness) sped up and reduced the depth of investigators' processing of criminal evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…Instead, our interpretation of these order effects is derived from Ask et al (), who showed that activating an efficiency goal (as opposed to a thoroughness goal) led to more biased evaluations of evidence. We can imagine that in the absence of a strong belief of guilt, incoming evidence is evaluated fairly thoroughly.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Instead, our interpretation of these order effects is derived from Ask et al (), who showed that activating an efficiency goal (as opposed to a thoroughness goal) led to more biased evaluations of evidence. We can imagine that in the absence of a strong belief of guilt, incoming evidence is evaluated fairly thoroughly.…”
Section: Discussionmentioning
confidence: 97%
“…But, E2 may be less likely to retroactively influence the evaluation of E1, because E1 has already been evaluated and is thus ‘anchored’ in place. Second, Ask, Granhag, and Rebelius () have shown that when evaluators have a goal to reach a conclusion quickly, they tend to reduce the depth of processing of subsequently presented evidence (and are hence more biased in their evaluation of it). Consider what this means for order effects.…”
Section: Presentation Ordermentioning
confidence: 99%
“…This becomes crucial when having to decide which instruction should be used to generate additional retrievals. In a recent study, Ask, Granhag, & Rebelius (2011) indicated that goal-directed processing activated at the time of the interview (i.e., thoroughness or efficiency) may have a strong influence on the investigator. An investigator focused on 'thoroughness' would know that even if a specific instruction does not generate a large amount of information, this little information can be very important to the success of the investigation; an investigator focused on 'efficiency' would probably reason from a 'value for money' perspective.…”
Section: Cost and Benefit Of Additional Recalls: Proposing New Measuresmentioning
confidence: 99%
“…The majority of studies have also been unable to examine the potential moderating effect of valence of evidence on context effects because they have either not manipulated the valence of the initial evidence (e.g., Dror et al, 2006;Miller, 1984), or did not include a no-initial-evidence control group (e.g., Ask et al, 2011; 1 . Studies that have been able to compare valences have shown a similar pattern to that observed here: Incriminating information has a larger effect on subsequent evidence evaluation than exonerating information .…”
Section: Evidence Evaluationmentioning
confidence: 99%
“…Second, Ask, Granhag, and Rebelius (2011) have shown that when evaluators have a goal to reach a conclusion quickly, they tend to reduce the depth of processing of subsequently presented evidence (and are hence more biased in their evaluation of it). Consider what this means for order effects.…”
Section: Presentation Ordermentioning
confidence: 99%